2006
DOI: 10.1111/j.1365-277x.2006.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet, blood lipid profile and physical activity patterns in primary school children from a semi‐rural area of Greece

Abstract: The findings from the present study support the worrisome trends that have been documented in Greek youngsters elsewhere, and predict an unfavourable cardiovascular risk profile for the Greek population in the foreseeable future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
9
1
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
6
9
1
5
Order By: Relevance
“…Although children are considered to be the most active population in our society, increased time spent on TV/video and computer games along with limited participation in physical education programs result in children's physical inactivity. Moreover, in a related study of our laboratory we found that boys spent significantly more time than girls on physical activity (Magkos et al, 2006). This was also confirmed in the present study, where the minutes of MVPA were 96.4982.1 for boys and 42.5947.6 for girls (P B0.01).…”
Section: Discussionsupporting
confidence: 93%
“…Although children are considered to be the most active population in our society, increased time spent on TV/video and computer games along with limited participation in physical education programs result in children's physical inactivity. Moreover, in a related study of our laboratory we found that boys spent significantly more time than girls on physical activity (Magkos et al, 2006). This was also confirmed in the present study, where the minutes of MVPA were 96.4982.1 for boys and 42.5947.6 for girls (P B0.01).…”
Section: Discussionsupporting
confidence: 93%
“…Considering other studies about the school-children population, our value of total energy intake of 11-to 14-year-old children was comparable to that of 12-year-old Greek children (9.82 8 1.84 vs. 8.37 8 3.06 MJ); on the other hand, there were noticeable differences in the energy percentages from fat and the structure of fatty acids. Daily intake of fat was high (42.0 en%), saturated fat consumption was elevated (15.6 en%), while polyunsaturated fat intake fell short (4.8 en%) for Greek students [21] , suggesting that values of Hungarian school children appear to be more favorable. Inadequate dietary fat structure could be disadvantageous in spite of a low level of daily total fat intake, as is manifested in the Isfahan Healthy Heart Program.…”
Section: Discussionmentioning
confidence: 95%
“…Nutritional habits are rooted in the early childhood, and can affect physical and mental development [5] , academic performance [19,20] as well as health status not only in childhood [21] but throughout the whole lifetime [4] , making it so important to get an adequate quantity and quality of food, especially in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…In Greece, the prevalence of obesity in adults, children and adolescents has been evaluated recently by some investigators (2)(3)(4)(5) . Moreover, research (6) shows that the dietary habits of Greek adults have changed towards a more Westernised type of diet, with some indication of this also being valid for children and adolescents (7,8) . The Westernisation of eating habits includes a reduced intake of dietary fibre, an increased intake of simple sugars and refined grain products, altered fat composition of the diet and a dietary pattern characterised by a high glycaemic load (9) .…”
mentioning
confidence: 99%